Experimental malaria-associated acute kidney injury is independent of parasite sequestration and resolves upon antimalarial treatment - Possemiers, Hendrik; Pollenus, Emilie; Prenen, Fran; Knoops, Sofie; Koshy, Priyanka; Van den Steen, Philippe E. (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria remains a severe global disease with more than 200 million cases and 600 000 deaths each year. Malaria-associated acute kidney injury (MAKI) may occur in up to 40% of patients with severe malaria and is associated with increased mortality. Histopathological characteristics of AKI in malaria are acute tubular injury, interstitial nephritis, focal segmental glomerulosclerosis, collapsing glomerulopathy and glomerulonephritis. We observed that C57BL/6 mice infected with Plasmodium berghei NK65 (PbNK65) develop MAKI in parallel with malaria-associated acute respiratory distress syndrome (MA-ARDS). MAKI pathology was associated with proteinuria, acute tubular injury and collapse of glomerular capillary tufts, which resolved rapidly after treatment with antimalarial drugs. With the use of skeleton binding protein-1 (SBP-1) KO PbNK65 parasites, we found that parasite sequestration and/or high parasite load are not required for the development of experimental MAKI. Parasite sequestration was not detected in the kidneys of both WT and SBP-1 KO infected mice. Similar proteinuria, histopathological features, and similar increased kidney expression of interferon-γ, TNF-α, kidney injury molecule-1 (KIM-1) and heme oxygenase-1 (HO-1) was observed in both infected groups despite a significant difference in parasite load. Taken together, we introduce a model of experimental AKI in malaria with important similarities to AKI in malaria patients. Therefore, this mouse model might be important to further study the pathogenesis of AKI in malaria.